Exergoeconomic assessment of a municipal primary and secondary sewage treatment. (9th November 2012) - Abusoglu, Aysegul; Demir, Sinan; Kanoglu, Mehmet
This paper presents the exergoeconomic analysis and assessment of a municipal primary and secondary sewage treatment systems. Operation of an existing municipal sewage treatment plant is described in detail and an exergoeconomic methodology based on SPECO method is provided to allocate cost flows through subcomponents of the plant. The system treats nearly 222, 000m³ domestic wastewater per day by using the primary and secondary treatment systems. The exergetic efficiencies of the primary and secondary sewage treatment systems are determined to be 53.4% and 14.8%, respectively. The exergetic cost rate and the specific unit exergetic cost of the treated wastewater at the exit of the WWTP are found to be 62.05 /h and 3.804 ¢/m³, respectively.